Physical and Chemical Characteristics of Combined Polyherbal Yogurt - Salmaa Sayyidah Nazziyah; Epi Taufik; Kintoko Kintoko (Jurnal Ilmu Pertanian Indonesia, 2025)
Yogurt has become a popular dairy product and is considered a promising candidate for functional food intake. Innovations in yogurt production continue to develop, increasing public interest in yogurt consumption by using herbal plants. The combination of active ingredients from multiple herbal plants may provide higher effectiveness compared to single herbal plants. Lactic acid fermentation in herbal plants significantly increases phenolic and flavonoid levels. This study aims to analyze the effect of polyherbal (green tea, fenugreek seed, and cinnamon) on yogurt with physical and chemical parameters. This study was conducted with the stages of making polyherbal extract, preparing polyherbal yogurt, and analyzing physical (viscosity) and chemical (pH, total titrated acid (TTA), total phenolic content, and total flavonoid content using a completely randomized design with four different polyherbal levels (0%, 1%, 2%, and 3%) in triplicates. Physical and chemical characteristics data were summarized using analysis of variance. The lactic acid fermentation process in yogurt form on polyherbal had a significant effect on chemical characteristics, such as pH, TTA, total phenolic and flavonoid contents. The best treatment level in this research is 3% polyherbal extract addition because it contains the highest total phenolic and flavonoid. Keywords: fermentation, Lactobacillus bulgaricus, polyherbal, Streptococcus thermophillus, yogurt